2019
DOI: 10.1093/omcr/omz069
|View full text |Cite
|
Sign up to set email alerts
|

Splenic sequestration crisis as an index manifestation of heterozygous hemoglobinopathy in an adult

Abstract: Sickle β+-thalassemia rarely manifests with acute splenic sequestration crisis in adults. We report a case of a 20-year-old female who presented with fever and left upper quadrant abdominal pain. Laboratory studies revealed hemolytic anemia. Tests for autoimmune hemolysis and hemolytic diseases were negative except for Hemoglobin (Hb) electrophoresis, which revealed sickle cell trait (Hb AS). Infectious workup was unremarkable. Computed tomography scan of the abdomen showed marked splenomegaly. The patient rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…A recent case of splenic sequestration reported by Edo-Osagie et al, revealed that the imaging findings described above can be explained histopathologically. Evaluation of the splenectomy specimen in that case revealed an enlarged spleen with peripheral subcapsular serpentine areas of necrosis and infarction, pooling of red blood cells in the splenic cords, and capillaries occluded with sickled red blood cells [18].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…A recent case of splenic sequestration reported by Edo-Osagie et al, revealed that the imaging findings described above can be explained histopathologically. Evaluation of the splenectomy specimen in that case revealed an enlarged spleen with peripheral subcapsular serpentine areas of necrosis and infarction, pooling of red blood cells in the splenic cords, and capillaries occluded with sickled red blood cells [18].…”
Section: Discussionmentioning
confidence: 90%
“…By adulthood, most individuals with HbSS have already undergone splenic infarction, fibrosis, and autosplenectomy, making splenic sequestration in adults an exceedingly rare phenomenon [5,21,22]. However, a small number of cases of splenic sequestration have been reported in adults with heterozygous sickle cell disease, including HbS/β + -thalassemia and sickle cell-hemoglobin C (HbSC), diseases in which splenomegaly often persists into adulthood [5,[7][8][9][10][11][12][13][14][15][16][17][18]22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may cause serious and life-threatening complications [13] [14] . Patients who were admitted to a hospital with complaints of stroke and sequestration were reported [12] [27] . Sequestration crisis is seen in HbSS or HbSβ 0 cases before the age of 5, while, in HbS/β cases, it may delay until puberty and early adulthood and progress rapidly, resulting in death as a result of hypovolemic shock [12] .…”
Section: Discussionmentioning
confidence: 99%